For Him, Art, Research, Creation and Politics Were the Same Thing: In Memory of Paul Boccara. (1st April 2019) - Herrmann, Peter
Abstract : Although the concept is a familiar one, it tends not to be fully accepted that economics, and political economy in particular, is in fact a social science. Focusing today on capital and commodities, economics does so in the light of their being social relationships. Paul Boccara, on whose work this article centres its attention, focused especially on the following concept: that social relations—both in general, and in the form of market relations—are interwoven with, and are expressions of, the rules of a general though historically specific human nature. Furthermore, we find even in so-called free market societies a complex apparatus that controls economic regulations, making them possible as well as determining their thrust. The article will explain how political life shaped Boccara personally, and how he in turn influenced the development of political economy, basing it firmly on the methodology of Karl Marx while applying it in new ways. The article also reflects on the need to consider the current crisis as a crisis of civilisation, one whose economic core is to be found in over-accumulation and devaluation on a global scale.